Vernacular Architecture of Austro-Asiatic Ethnic Groups in Thailand, Based on the Encyclopedia of Vernacular Architecture of the World - Buranaut, Isarachai; Kirdsiri, Kreangkrai (Journal of Mekong Societies, 2016)
This review analyzes two main aspects of the vernacular architecture of Austro-Asiatic ethnic groups in Thailand based on the Encyclopedia of Vernacular Architecture of the World. The emphasis is on theories and principles so as to make comparisons and conclusions. Relevant documents on vernacular architecture of Austro-Asiatic groups in Thailand were collected, then categorized as specified in the Encyclopedia of Vernacular Architecture of the World, consisting of the following: 1) concepts, 2) cultural and general aspects, 3) surroundings, 4) materials and resources for construction, 5) products and construction details, 6) maintenance, 7) signs and decoration, 8) categories, and 9) uses and functions. The comparison was done to evaluate existing knowledge; it was then categorized, based on the above theories and principles. Gaps will be examined and guidelines will be proposed.